TINJAUAN BERKAS KLAIM TERTUNDA PASIEN JKNRUMAH SAKIT HERMINA CIPUTAT 2018 - Supriadi, Supriadi; Rosania, Syifa (Jurnal Vokasi Indonesia, 2019)
This study was done to look at the picture of pending claims that were returned by the BPJS Kesehatan and its causes at Hermina Ciputat Hospital, Tangerang Selatan Banten. This research is descriptive with a qualitative approach. The data used were the claim files from inpatient and outpatient treatment that was delayed or returned by BPJS Health in June-August 2018. The variables used in this study are the number of pending claim files, reasons for returning and the reasons for cause of the returning. The findings showed there are 142 file claims for inpatient and 82 outpatient files were returned. Reason for returning because it did not pass the administrative verification of service and verification of health service. The cause of not passing verification was mainly due to inaccuracy of the filing officer and the existence of different perceptions of the diagnosis code between Hermina Ciputat Hospital and BPJS Kesehatan. The results of this study can be an evaluation for Hermina Ciputat Hospital to improve the system of filing claims for BPJS Kesehatan patients in order to reduce the number of claim files returned by BPJS Kesehatan